Local development in rural areas (Polis (Santiago), 2018)
This article argues that rethinking a new development is the challenge in these times of crossroads, which requires a critical reading of the theories that will allow us to learn to unlearn. Points out that new Latin American realities manifest as a result of three axis- processes: Globalization and the effects of economic integration processes, the difficulties in the democratic organization of collective life, and the social inequalities. The paper criticizes the fact that today liberal capitalism is glorified as the only possible and desirable economic model, which alone would ensure the continuity of democracy; and argues that the new reality that moves between social innovation and the return to the territory, requires modification of the individual and collective mentalities and involves a vast training of local staff and local people. After presenting some experiences in Latin America, the author concludes that only in a new culture of development with the commitment to build a world of harmony between urban life and rural areas, between South and North, it may ne possible to make sense to policies and actions.
Keywords: new development; Latin America; globalization; urban life; rural areas